Increased vimentin mRNA expression in MCF-7 breast cancer cell line after repeated endoxifen-treatment (Medical Journal of Indonesia, 2016)
Background: Epithelial mesenchymal transition (EMT) plays a significant role in the development of cancer cell resistance to drugs. Vimentin, a type III intermediate filament protein, is a marker of EMT. Vimentin's over-expression in cancer correlates well with increased tumor growth, change in cell shape and poor prognosis. Endoxifen is an active metabolite of tamoxifen and has become a new potent agent in the treatment of breast cancer. This is a study that aimed to investigate the effect of endoxifen exposure with or without estradiol on cell viability, cell morphology and EMT progression through the analysis of vimentin mRNA expression after 4-week treatment. Methods: Endoxifen, 100 nM or 1,000 nM, with or without beta-estradiol were given repeatedly to MCF-7 cells. Cells treated with dimethyl sulfoxide (DMSO) 0.001% were used as control. After 2- and 4-week exposure, the cells were counted, analyzed for mRNA vimentin expression, and observed for morphological changes. Results: Compared to control, there were significant decreases in vimentin mRNA expressions in endoxifen and endoxifen+β-estradiol treated cells after 2-weeks, which then significantly increased after 4-week compared with the 2-week exposure. We found no change in morphology of MCF-7 cells. Conclusion: Repeated exposure of endoxifen might induce EMT progression through increased expression of vimentin in MCF-7 breast cancer cell line.